Research on Integration of Emotion Analysis in English Modular Teaching Based on Natural Language Processing - Su, Fuxing (Frontiers in Psychology, 2022)
Now, the application of intelligent technologies such as machine learning and deep learning in natural language processing has achieved good results. This paper studies the integration of emotion analysis in English module teaching of natural language processing. Vocabulary is a very important part in English teaching. Learning vocabulary well can improve students' reading ability. However, in the process of students' learning, vocabulary is the most basic and difficult to learn. Poor vocabulary learning and insufficient accumulation will restrict students' reading ability. Improving vocabulary teaching mode and learning methods can stimulate students' interest in learning and effectively improve their reading ability. In the third part of the article, the neural network language model and statistical model are used to analyze the key technologies of natural language processing, and then the Naive Bayes algorithm and support vector machine model algorithm are used to optimize the data; Finally, two classes are selected for comparative experiment, Then, by integrating emotional teaching into students' classroom and analyzing students' interest, the conclusion is that integrating emotional teaching in teaching can effectively improve students' academic achievements, and at the same time, integrating emotional teaching in teaching can also stimulate students' enthusiasm for learning English and effectively change students' learning attitude.